Placenta Accreta - Al-Saadi, Zahida (Journal of the Faculty of Medicine Baghdad, 2007)
Placenta accrete is defined as an abnormally adherent placenta that is directly attached to the myometrium because of inadequate development of the fibrinoid layer (Nitabuch layer) and absence of decidua basilis either partially or totally. (1) Three degrees of placenta accrete exist depending on the depth of villous invasion: placenta accreta is when villibecome attached to myometrium, placenta increta: the villi invade the myometrium, placenta percreta represents the greatest degree of severity where placental villi penetratethroughout myometrium and peritoneum extending sometimes to adjacent structure such as the bladder. (1, 2, 3)Placenta accreta accounts for 78% of cases, increta for 17% and percreta 5- 7 %.( 4) Massive obstetric hemorrhage is still the leading cause of pregnancy related deaths, and placenta previa accreta remains one of the serious predisposing factors. (5)The problem occurs when there is abnormal separation of placenta in 3rd stage of labor, and attempts to deliver the placenta may provoke massive blood loss that may necessitatehysterectomy. (2) With the increasing rate of cesarean section the incidence of both placenta previa and placenta accreta is steadily increasing in frequency, (3, 4) wetherefore anticipate more cases of placenta previa accreta. In several recent series, placenta accreta has emerged as the major indication for peripartum  hysterectomy, accounted for 40-60% of cases. (7), It is not always clinically possible to differentiate between the three types of placenta accreta.Placenta accreta is not usually suspected when the placenta is normally situated, but antenatal diagnosis is possible when placenta accreta is previa. Accreta invasion may involve whole placental cotyledons, or partial (several cotyledons), or focalas one or two cotyledons.